PROBLEMATIKA ADAT DALAM NOVEL MEMANG JODOH KARYA MARAH RUSLI DAN PERBANDINGANNYA DENGAN BUDAYA MINANGKABAU - Yosi Wulandari (Pendidikan Bahasa dan Sastra Universitas Muhammadiyah Purworejo, 2016)
ABSTRACT:This study aimed to describe two ways, as follows. (1) The description of the problems of the indigenous in the novel Memang Jodoh. (2) Comparison of the problems of the indigenous in the novel Memang Jodoh with the value of traditional Minangkabau culture. This research was a qualitative study with content analysis method. The results of this study are as follows. (1) The problems of the indigenous in the novel